A low kickback fully differential dynamic comparator for pipeline analog‐to‐digital converters. Issue 4 (10th November 2019) - Diaz‐Madrid, Jose‐Angel; Domenech‐Asensi, Gines; Hauer, Johann; Mateu, Loreto
Abstract : This study presents a fully differential dynamic comparator with low kickback noise, an effect caused by voltage variations in the regeneration nodes of these types of circuit. Given their low power dissipation, dynamic comparators are key circuits in analog‐to‐digital converters (ADCs), especially in pipelined ADCs. The proposed comparator has been simulated and compared with three other comparator topologies. The value of the kickback noise generated by the proposed circuit is lower than that generated by other conventional dynamic comparators over a wide input range, while simultaneously showing a low offset voltage error. The dynamic comparator has been implemented in a low‐resolution ADC with a resolution of 2.5 effective bits, which has been prototyped in a 0.35‐ μ m CMOS AMS C35B4 process. Its size is 34 μ m × 38 μ m .